Formação acadêmica do terapeuta ocupacional no campo da saúde mental - Lins, Sarah Raquel Almeida (2015)
The National Curriculum Guidelines for the Bachelor s degree in Occupational Therapy (Diretrizes Curriculares Nacionais do Curso de Graduação em Terapia Ocupacional (DCNTO) in Brazil was created in 2001 and had as one of its propositions the development towards public health. During this time, with the creation of territorial services, the mental health care started to be based on the Psychosocial Rehabilitation assumptions. Recent studies have shown that students who have finished Occupational Therapy (OT) undergraduation and work in the field of mental health report that theoretical and practical training given throughout undergraduation was not adequate facing the real demand. This study aims to understand the real condition of occupational therapists training during undergraduation and its connection with Brazilian public policies and the guidelines in the mental health field. It is a descriptive cross-sectional study, with both qualitative and quantitative approach, which involved the participation of 135 students and newly graduates, and courses in mental health, all related to ten OT graduation programmes in São Paulo State, Brazil. The data collection involved documentary analysis of materials provided by the programme coordinators: documental forms, Pedagogy and Policy Projects, syllabi of courses related to mental health; semistructured interviews with the professors; and questionnaire given to students and newly graduates. The documentary information was organized and the questionnaire and interview data were used, respectively, for category and thematic analysis. The results indicate that the internship in mandatory in mental health among the majority of the schools participating in the study and, in general, the sites comply with the SUS (Sistema Único de Saúde Unified Health System) requirements. It is also observed that the students and newly graduates feel relatively confident for the practice in the mental health field; they know the publics policies and understand that there is a lack between them and the reality found in the places available for their professional practice. They report to be more confident in relation to: multidisciplinary teamwork, being able to assist in general health, and plan the treatment based on a broader aspect regarding the subject s needs in his daily life. On the other hand, they feel more insecure to leading a team and managing mental health services. Professors further the remarks in regards to the challenges in training and highlight the need of approaching a more diverse and complex both theoretical and practical contents of the curriculum guidelines. Besides, they consider that the general training is the most appropriate and relevant during this stage and consider the continuing education to be a way to guarantee the necessary elements to perform professionally. It is argued that, despite of its conditions, the programmes follow the DCN-TO ans make efforts to offer a training closer to authentic practice environment in order to have a professional who can make a difference and work under the SUS guidelines. It is believed that this study may contribute for occupational therapist s understandings about practical and theoretical training in mental health and for making considerations between public health policies and professional training during undergraduation, as well as offer assistance to guideline improvements.